2018
DOI: 10.1038/s41467-018-06705-0
|View full text |Cite
|
Sign up to set email alerts
|

A missense variant in SLC39A8 is associated with severe idiopathic scoliosis

Abstract: Genetic factors predictive of severe adolescent idiopathic scoliosis (AIS) are largely unknown. To identify genetic variation associated with severe AIS, we performed an exome-wide association study of 457 severe AIS cases and 987 controls. We find a missense SNP in SLC39A8 (p.Ala391Thr, rs13107325) associated with severe AIS (P = 1.60 × 10−7, OR = 2.01, CI = 1.54–2.62). This pleiotropic SNP was previously associated with BMI, blood pressure, cholesterol, and blood manganese level. We replicate the association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 40 publications
2
49
2
Order By: Relevance
“…No differences were detected in any of the other trace elements transported through SLC39A8 (Zn, Co, and Cu), though effects on Cd could not be assessed as levels were below our method of detection limit. Fe was not measured in our study, though GWAS on Fe levels and Fe-related traits have not identified any associations with the A391T missense variant, and two recent studies show no difference in Fe concentration in A391T carriers, suggesting that serum Fe is not affected (9,46) Multiple studies demonstrate the importance of SLC39A8 to health and disease. Hypomorphic mice expressing 10-15% of basal SLC39A8 show severe growth stunting, dysmorphogenesis, and anemia (47,48).…”
Section: Discussioncontrasting
confidence: 53%
“…No differences were detected in any of the other trace elements transported through SLC39A8 (Zn, Co, and Cu), though effects on Cd could not be assessed as levels were below our method of detection limit. Fe was not measured in our study, though GWAS on Fe levels and Fe-related traits have not identified any associations with the A391T missense variant, and two recent studies show no difference in Fe concentration in A391T carriers, suggesting that serum Fe is not affected (9,46) Multiple studies demonstrate the importance of SLC39A8 to health and disease. Hypomorphic mice expressing 10-15% of basal SLC39A8 show severe growth stunting, dysmorphogenesis, and anemia (47,48).…”
Section: Discussioncontrasting
confidence: 53%
“…In silico modeling predicts rs13107325 to be in the top 1.4% of deleterious substitutions in the human genome ( 2 ). The major allele associates with an increased risk of Parkinson’s disease, hypertension ( 3 ), and alcohol misuse disorders ( 4 ), and the minor allele associates with increased risk of schizophrenia ( 5 ), Crohn’s disease ( 6 ), obesity ( 7 ), dyslipidemia ( 8 ), and scoliosis ( 9 ). The minor allele frequency (MAF) is approximately 0.05 in American population and, 0.08 in Northern European populations and increases to 0.14–0.25 in the Ashkenazi Jewish population; the major allele is monomorphic in African and East and South Asian populations ( 10 – 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…5 The solute carrier 39 (SLC39) gene family encoding the Zinc IRT-like Proteins (ZIPs) contribute to cellular metal and zinc homeostasis by encoding proteins that mediate cation influx or transport from intracellular compartments. 6 Mutations in the ZIP transporter family have been linked to various genetic disorders, such as acrodermatitis enteropathica, 7,8 schizophrenia, 9 scoliosis, 10 intellectual disability, [11][12][13] Crohn's disease, 14 Ehlers-Danlos syndrome, 15 and parkinsonism-dystonia. 16 Given the wide roles for zinc in many biochemical processes, the genes regulating cellular zinc homeostasis can impact diverse processes of the nervous system.…”
Section: Introductionmentioning
confidence: 99%